Companies don't succeed people do! : ideas to cteate profits through people - Roberts-Phelps, Graham (London : Hawksmere, 2000)
This text features 100 positive and practical ideas that canbe put to work immediately to build a stronger, fitter and more profitable business. It includes such topics as: be passionate about business; the customer is not always right; and close the customer service department.
oif 28/01/15
Loan
Keywords: Management; Industrial management; Success in business; Business strategy